Effect of gas flaring, oil rent and fossil fuel on economic performance: The case of Nigeria. (August 2022) - Okoye, Lawrence Uchenna; Adeleye, Bosede Ngozi; Okoro, Emmanuel E.; Okoh, Johnson I.; Ezu, Gideon K.; Anyanwu, Felicia A.
Abstract: The study investigates the effect of gas flaring, oil rent and fossil fuel on economic growth in Nigeria from 1990 to 2019 using the autoregressive distributed lag error correction (ARDL-ECM) representation. The fully modified ordinary least squares (FMOLS) and Canonical cointegration regression (CCR) methods are used to check for robustness of the estimates. From the ARDL-ECM results, the study highlights that in the long-run there is significant positive contribution of oil rent, gas flaring and fossil fuel production. For the most part, the outcomes of the FMOLS and CCR align with our findings except that gas flaring showed to depress economic performance. Following these, we sustain the argument that the oil-led and fossil-led growth hypotheses hold. Thus, both the oil sector and use of fossil energy are the major drivers of economic activities in Nigeria. We therefore conclude that, within the scope of our study, natural resource curse or Dutch disease hypothesis is not validated. The authors recommend that the economic gains from Nigeria's rich natural endowments be consolidated through well thought-out diversification programs for economic sustainability. Appropriate policies should also be developed and implemented towards incremental reduction, and ultimate elimination of gas flaring. Highlights: Flaring, oil rent and fossil fuel effect on economic growth over 38 years was studied. ARDL, fully modified OLS and canonical regression methods are used. Significant positive contribution of oil rent and fossil fuel to the economy was observed. Gas flaring did not depress economic performance.